The Relationship Between Mastery Orientation and Maximal Oxygen Uptake Among Military Cadets: The Mediating Role of Intrinsic Motivation. (1st October 2016) - Buch, Robert; Dysvik, Anders; Kuvaas, Bård; Säfvenbom, Reidar
ABSTRACT: Drawing upon achievement goal theory (AGT) and self-determination theory (SDT), a longitudinal study was conducted among 248 military cadets across a two-year time span. The results showed that mastery orientation at Time 1 was positively associated with intrinsic motivation at Time 2 after controlling for intrinsic motivation at Time 1. Furthermore, intrinsic motivation assessed at Time 2 was positively associated with maximal oxygen uptake (VO2 max) at Time 3 after controlling for VO2 max at Time 2. This suggests that military cadets who strive to improve their personal performance (i.e., mastery-oriented individuals) are more likely to exhibit an increase in their level of VO2 max and that this increase can be attributed to increased intrinsic motivation.